Budaya Lokal sebagai Sarana Pemulihan Trauma: Sebuah Studi pada Generasi Z di Indonesia - Salsabila Zafila, Salma; Purnairawan, Riski Eka (Saneskara: Journal of Social Studies, 2024)
This study aims to explore how local cultural practices, such as traditional rituals, art, and communal activities, can support the trauma recovery process for Generation Z. The research is grounded in the belief that these practices provide not only emotional and spiritual support but also enhance a sense of identity and community belonging, which are vital for the psychological well-being of this generation. Utilizing a systematic literature review (SLR) methodology, the study focuses on articles published in the last five years, with data collected through extensive searches of academic databases like Scopus, Web of Science, PubMed, and Google Scholar. Articles were selected based on their relevance to the use of local cultural practices in trauma recovery for Generation Z, and content analysis techniques were employed to identify common themes and trends. The findings highlight that local cultural practices offer frameworks for emotional expression and social reintegration, essential for trauma recovery. Specifically, rituals such as community healing ceremonies and traditional arts like dance and music provide structured outlets for processing traumatic experiences. These practices, deeply embedded in communal values, help restore normalcy and continuity for trauma-affected individuals. Additionally, participation in these cultural activities significantly reduces feelings of isolation and strengthens social support networks, which are crucial for psychological resilience. The study underscores the importance of integrating local cultural practices into trauma recovery programs, advocating for culturally sensitive approaches that align with the values and beliefs of the community, particularly in the Indonesian context for younger generations.